Development of a Chiral N-Alkoxyamide Strategy and Application to the Asymmetric Total Synthesis of Fasicularin - Minamikawa, Ryo; Fukaya, Keisuke; Kobayashi, Akihiro; Komiya, Yukinori; Yamamoto, Shio; Urabe, Daisuke; Chida, Noritaka; Sato, Takaaki (Synthesis, 2021)
The asymmetric total synthesis of fasicularin by a chiral N-alkoxyamide strategy is reported. Incorporation of the chiral alkoxy group onto an amide nitrogen changes the original reactivity of the amide, enabling two key transformations: aza-spirocyclization and the reductive Strecker reaction. DFT calculations indicate that pyramidalization of the N-alkoxyamide nitrogen is crucial to produce a cyclic hemiaminal in equilibrium, which undergoes aza-spirocyclization. The chiral alkoxy group is also used as a stereocontrol element to establish two consecutive stereocenters. The iridium-catalyzed reductive Strecker reaction of the N-alkoxylactam provides the aminonitrile with high diastereoselectivity.
Keywords: amides; DFT calculations; fasicularin; heteroatom–heteroatom bonds; nucleophilic addition; remote stereocontrol; total synthesis